A comparative study of biodiesel production methods for Reutealis trisperma biodiesel - Silitonga A.S.; Mahlia T.M.I.; Ong H.C.; Riayatsyah T.M.I.; Kusumo F.; Ibrahim H.; Dharma S.; Gumilang D. (Taylor and Francis Inc., 2023)
Esterification; Esters; Surface properties; Transesterification; Biodiesel production; Catalyst concentration; Laboratory experiments; Optimum process conditions; Physicochemical property; Reaction temperature; Response surface methodology; Reutealis trisperma; Biodiesel